The degeneration-pain relationship in the temporomandibular joint: Current understandings and rodent models - Chung, Man-Kyo; Wang, Sheng; Alshanqiti, Ishraq; Hu, Jiaxin; Ro, Jin Y. (Frontiers in Pain Research, 2023)
Temporomandibular disorders (TMD) represent a group of musculoskeletal conditions involving the temporomandibular joints (TMJ), the masticatory muscles and associated structures. Painful TMD are highly prevalent and conditions afflict 4% of US adults annually. TMD include heterogenous musculoskeletal pain conditions, such as myalgia, arthralgia, and myofascial pain. A subpopulations of TMD patients show structural changes in TMJ, including disc displacement or degenerative joint diseases (DJD). DJD is a slowly progressing, degenerative disease of the TMJ characterized by cartilage degradation and subchondral bone remodeling. Patients with DJD often develop pain (TMJ osteoarthritis; TMJ OA), but do not always have pain (TMJ osteoarthrosis). Therefore, pain symptoms are not always associated with altered TMJ structures, which suggests that a causal relationship between TMJ degeneration and pain is unclear. Multiple animal models have been developed for determining altered joint structure and pain phenotypes in response to various TMJ injuries. Rodent models of TMJOA and pain include injections to induce inflammation or cartilage destruction, sustained opening of the oral cavity, surgical resection of the articular disc, transgenic approaches to knockout or overexpress key genes, and an integrative approach with superimposed emotional stress or comorbidities. In rodents, TMJ pain and degeneration occur during partially overlapping time periods in these models, which suggests that common biological factors may mediate TMJ pain and degeneration over different time courses. While substances such as intra-articular pro-inflammatory cytokines commonly cause pain and joint degeneration, it remains unclear whether pain or nociceptive activities are causally associated with structural degeneration of TMJ and whether structural degeneration of TMJ is necessary for producing persistent pain. A thorough understanding of the determining factors of pain-structure relationships of TMJ during the onset, progression, and chronification by adopting novel approaches and models should improve the ability to simultaneously treat TMJ pain and TMJ degeneration.